EL PROGRAMA DE CAPACITACIÓN EMPRESARIAL SE RELACIONA CON EL DESEMPEÑO LABORAL CASO: TRABAJADORES DEL FONDO DE EMPLEADOS DEL BANCO DE LA NACIÓN - Mayurí Barrón, Jorge Vicente (2011)
Today there is a high competitive pressure, this makes the companies have to align with their competence and even more with the wishes of customers, which is why companies are created, many companies find that to be updated on the progress competitive must consider only the maintenance of its various resources such as materials, equipment and others, many of them forget that human potential requires their respective update, thus the creation of corporate training programs in line with what the market is required important as this will enhance job performance and hence labor productivity.